Quality of life in obstructive sleep apnea-hypopnea syndrome (OSAHS) - Natalia Londoño-Palacio; Franklin Escobar-Córdoba; Maria Eugenia Toro-Pérez (Revista de la Facultad de Medicina, 2017)
Obstructive sleep apnea-hypopnea syndrome (OSAHS) has a direct influence on the quality of life of people who suffer from it. Objectively measuring this impact at diagnosis and during treatment is important to improve the subsequent adherence to treatment. Based on different studies, general and specific disease scales for OSAHS have been created, which allow to evaluate different dimensions such as daytime symptoms, nocturnal symptoms, daytime sleepiness, emotions, the repercussion of the disease on the social interactions of people, as well as the patient’s perception of the treatment indicated.